Expert Answers

An illustration of the letter 'A' in a speech bubbles

the natural log of e^x is x. Thus:

ln(e^x) = x

ln(e^2) = 2

ln (e^7) = 7

So this equation becomes:

x - 2 = 7

x = 9

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

ln e^x - ln e^2 = ln e^7

We know that ln e^x = xlne

Also we know that ln e = 1

Now let us substitute:

x ln e -2ln e = 7 ln e

x*1 -2*1 = 7*1

==> x-2 = 7

Add 2 to both sides:

==> x = 7+2 = 9

The answer is x=9

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial